2013
DOI: 10.1007/s13139-013-0243-3
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment F-18 FDG PET/CT Parameters to Evaluate Progression-Free Survival in Gastric Cancer

Abstract: In gastric cancer, SUVmax measured by pretreatment F-18 FDG PET/CT has a significant predictive value for PFS. In addition, if MTV is measurable, high MTV is an independent factor for disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…For the determination of the cutoff values for high and low SUVs, five studies [15, 16, 2426] used the receiver-operating characteristic (ROC), two studies [4, 14] used medians as the threshold values and one study [23] used averages as the cutoff values. The primary characteristics of the enrolled studies are presented in Table 1 and detailed information of the PET protocol is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…For the determination of the cutoff values for high and low SUVs, five studies [15, 16, 2426] used the receiver-operating characteristic (ROC), two studies [4, 14] used medians as the threshold values and one study [23] used averages as the cutoff values. The primary characteristics of the enrolled studies are presented in Table 1 and detailed information of the PET protocol is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…1 In the past few decades, significant progress has been achieved in using diagnostic techniques and treatment regimens to improve the survival of patients with GC. [2][3][4][5][6] However, the survival of these patients could be further improved, particularly through the discovery of widely available and inexpensive biomarkers for the diagnosis, determination of the prognosis, determination of the requirement for adjuvant therapy, and monitoring of therapeutic responses. In recent years, some studies have explored the relationship between different inflammatory markers and the prognosis of patients with GC.…”
Section: Introductionmentioning
confidence: 99%
“…There are some conflicting findings with regard to whether 18F-FDG PET plays an important role as a predictive or prognostic factor in SCLC. Several studies have reported that high SUV values in 18F-FDG PET as a prognostic factor are associated with a poorer clinical outcome in patients with various malignancies, such as head-and-neck cancer, renal cell carcinoma, cervical cancer, gastric cancer and also non-SCLC (Berghmans et al 2008;Hentschel et al 2011;Dholakia et al 2013;Kim et al 2014;Liu et al 2015).…”
Section: Discussionmentioning
confidence: 99%